Properties of In2S3‐Based pin‐Heterojunctions. Issue 11 (25th March 2018) - Jawinski, Tanja; Wägele, Leonard A.; Scheer, Roland; Grundmann, Marius; von Wenckstern, Holger
Abstract : Undoped and vanadium‐doped In2 S3 is used to fabricate pin ‐diodes. As p ‐type semiconductor two materials are compared: nano crystalline NiO and amorphous zinc‐cobalt‐oxid (ZCO). n ‐ZnO:Al (AZO) is used as electrode to In2 S3 . In2 S3 ‐films are grown by co‐evaporation, NiO‐ and ZCO‐films by pulsed laser deposition (PLD) and ZnO:Al‐films by RF sputtering. The diodes exhibit high current rectification of up to 3 and 6 orders of magnitude at ±2 V for diodes with p ‐NiO and p ‐ZCO, respectively. Diodes with p ‐type ZCO are used for solar cell analysis. Upon illumination both solar cell types with undoped and V‐doped In2 S3 as absorber material show photovoltaic activity. We find open‐circuit voltages of up to 300 mV and short‐circuit current densities of up to 0.29 mA cm −2 . Abstract : Heterostructure diodes are fabricated using undoped and vanadium‐doped In2 S3 . An electrode to In2 S3 is formed by n ‐type ZnO:Al. To receive pin ‐structures p ‐type zinc‐cobalt‐oxid (ZCO) or NiO are used. Electrical properties of these diodes are studied and demonstrate high rectifications. Electrical characterizations under illumination of devices with p ‐type ZCO reveal that they can be used as solar cells.